Sweat control in male by the use of alunogen and cypripedium pubescens - Lorenzo Martini (Our Dermatology Online, 2015)
Aim of my study is to investigate upon the quality and quantity of the free fatty acids secreted by apocrine glands, as chief index to determine the real efficacy of a new model of antiperspirant-deodorant, that interferes directly with apocrine glands (by reducing drastically the secretion of free fatty acids) and indirectly with eccrine glands, by minimising the salted water secretion. I created an innovative cosmetic formula that comprises the Alunogen, idest the heptadecahydrated form of aluminium sulphate, since the generic aluminium sulphate has been recently accused of the onset of the Alzheimer's disease, when penetrating the epidermis, although definitive scientific proof is difficult to establish due to the lack of longitudinal studies, and therefore could be banished in the very next future. The formula comprises also the concrète of Cypripedium Pubescens (Lady's slipper) which contains, inter alia, the cypripedin, a quinine-analog, endowed by anticholinergic activities, that can be reputed useful as astringent agent with regards to eccrine glands, synergically to the action upon apocrine glands performed by alunogen. I recruited 11 young men, 11 bricklayers that customarily have to work 9 hours pro day after the hot summer sun and assert without doubt to sweat copiously, in order to carry out my experience.